Improving Students’ Reading Comprehension through Guessing Strategy - Dewi Fatimah Sitompul; Eka Sustri Harida; Sojuangon Rambe (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
The purposes of this research were: to describe the students’ reading comprehension through guessing strategy and to identify the factors which influenced students’ reading comprehension through guessing strategy at Grade XI MAS Darul Istiqomah Hutapadang - Pijorkoling. This research used classroom action research consisted of two cycles. Moreover, the participants of this research were the class of XI (19 students) and there was collaboration with an English teacher. Meanwhile, the data was derived from reading comprehension tests, observation, and interview. Students’ score in cycle 1 was 62.24 (4%) and students’ score in cycle 2 was 78.68 (79%). Based on the research result in cycle 1 and cycle 2, it showed the improvement of students’ mean score and students’ percentage. So, students’ improvement in reading comprehension through guessing strategy was good category (high).